Peran Ganda Perempuan Dalam Keharmonisan Rumahtangga - Djunaedi Djunaedi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2018)
The purpose of this research is to know the double role of women in household harmony. This type of research used descriptive qualitative analysis research. Data collection techniques used: 1) interview, 2) observation, 3) literature study. The results showed that the problems faced by households have had an impact on economic aspects both on family income. In the process of activity classified as harmonious because women who play a double role can carry out 2 (two) functions at once, that is taking care of the household and also work to earn income and increase family income. Factors that cause women to play a double role is to help the husband supplement family income and earn a living in addition to career. The efforts of women who play a dual role in family household harmony is to respect or respect the husband as the leader or head of household and open attitude in communicating to face every problem of household and devote the love to husband and children.